Randomized phase II trial in prostate cancer with hormone-sensitive OligometaSTatic relapse: Combining stereotactic ablative radiotherapy and durvalumab (POSTCARD GETUG P13): Study protocol. (May 2023) - Rogé, Maximilien; Pointreau, Yoann; Sargos, Paul; Meyer, Emmanuel; Schick, Ulrike; Hasbini, Ali; Rio, Emmanuel; Bera, Guillaume; Ruffier, Amandine; Quivrin, Magali; Chasseray, Mathieu; Latorzeff, Igor; et al.
Highlights: POSTCARD is a randomized multicentric phase II trial. Including patients with prostate cancer and hormone-sensitive oligometastatic relapse. Treated with stereotactic body radiotherapy alone (SBRT) (Control group) Or SBRT and Durvalumab (anti PD-L1) (Experimental group) We expected longer life expectancy with acceptable toxicity in experimental group. Abstract: Background: As in other solid tumors, increasing evidence indicates that patients diagnosed with a limited number of prostate cancer metastases, so-called oligometastases, have a better prognosis than patients with extensive metastatic disease. Stereotactic body radiotherapy (SBRT) is now considered an option in this population. Programmed death-1 (PD-1) and its ligands (PD-L1) are targeted by immune checkpoint inhibitors. Preclinical studies have shown that the tumor immune microenvironment changes when combining radiotherapy with immunotherapy, especially with hypofractionated radiotherapy. The oligometastatic setting appears to be the most relevant clinical situation for evaluating the immune response generated by radiotherapy and immune checkpoint inhibitors in patients with an intact immune system. We hypothesize that durvalumab will enhance the immune response following SBRT targeting oligometastatic lesions. Our purpose is to demonstrate, via a randomized 2:1 phase II trial, that SBRT (3 fractions) with durvalumab in oligometastatic hormone-sensitive prostate cancer patients would improve progression-free survival in patients with prostate cancer with up to 5 metastases compared to patients who exclusively received SBRT. Methods: This is a multicentric randomized phase II study in French academic hospitals. Patients with prostate cancer and up to 5 metastases (lymph node and/or bone) were randomized into a 2:1 ratio between Arm A (experimental group), corresponding to durvalumab and SBRT to the metastases, and Arm B (control group), corresponding to SBRT alone to the metastases. The study aims to accrue a total of 96 patients within 3 years. The primary endpoint is two-year progression-free survival and secondary endpoints include androgen deprivation therapy-free survival, quality of life, toxicity, prostate cancer specific survival, overall survival, and immune response. Discussion: The expected benefit for the patients in the experimental arm is longer life expectancy with acceptable toxicity. We also expect our study to provide data for better understanding the synergy between immunotherapy and radiotherapy in oligometastatic prostate cancer.